Fuerzas Económicas y Desempeño de Mercado de Valores para la Comunidad Andina, Periodo 2005 – 2019. - Luis Samuel, Sislema Cujilema (2022)
ABSTRACT The purpose of this paper is to identify the economic forces that affect the performance of the Andean Community stock market, period 2005-2019, both in the short and long term, taking into consideration the Stock Index (KSI) as a dependent variable and economic forces as independent variables. It has shown that the Economic Forces analyzed as Exchange Rate (TC), Gross Domestic Product (GDP), Inflation (INF), Oil Price (WTI), and the Money Supply (OM) present continuous periods of volatility in similar periods these being convergent with each other and the stock market, revealing that the economic forces analyzed do not guarantee appropriate performance of the stock market, thereby manifesting to investors liquidity variations, continuous periods of risk and fluctuations in profitability. In the same way, it establishes that the econometric model to estimate, is an error correction model (VEC) thus series does not present stationarity in their levels showing cointegration, being evidence that there is no relationship in the long term, where the LOGMCAP series, LOGMCAP, LOGMTV, LOGOM, LOGPIB AND LOGTWI, show significance in the performance of the stock market, the unidirectional existence of causality in the sense of Granger is determined, which indicates that only the variable Market capitalization (MCAP) cause the stock market. Finally, it shows that a positive shock to GDP, WTI, affects the growth of the KSI. Keywords: stock market, macroeconomic factors, Andean Community, investors, economic growth. Reviewed by: Lic. Eduardo Barreno Freire ENGLISH PROFESSOR C.C. 0604936211